2020
DOI: 10.1302/2046-3758.16.bjo-2020-0053.r1
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and orthopaedic team members’ mental health during the COVID-19 pandemic

Abstract: Aims Healthcare systems have been rapidly restructured to meet COVID-19 demand. Clinicians are working to novel clinical guidelines, treating new patient cohorts and working in unfamiliar environments. Trauma and orthopaedics (T&O) has experienced cancellation of routine clinics and operating, with redistribution of the workload and human resources. To date, no studies have evaluated the mental health impact of these changes on the T&O workforce. We report the results of a novel survey on the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 13 publications
1
12
1
4
Order By: Relevance
“…Compared to male participants, female participants found it more challenging to manage their anxiety levels, particularly regarding the inadequate availability of PPE during the COVID-19 pandemic. These results are corroborated by a UK study conducted on orthopedic members [ 40 ]. The underlying association of female gender with a higher incidence of generalized anxiety across different countries was evident in a systematic review by Remes et al [ 41 ].…”
Section: Discussionsupporting
confidence: 80%
“…Compared to male participants, female participants found it more challenging to manage their anxiety levels, particularly regarding the inadequate availability of PPE during the COVID-19 pandemic. These results are corroborated by a UK study conducted on orthopedic members [ 40 ]. The underlying association of female gender with a higher incidence of generalized anxiety across different countries was evident in a systematic review by Remes et al [ 41 ].…”
Section: Discussionsupporting
confidence: 80%
“…A Data reported as number of respondents (% of respondents). mental health survey of orthopaedic team members in the United Kingdom during the COVID-19 pandemic found that the prevalence of GAD and MDD was almost three times and six times greater respectively than the general population [12]. These studies re-enforce the importance of providing mental health support to doctors during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 89%
“…A study by British Medical Association (BMA) during the COVID-19 pandemic found that of doctors were dealing with depression, anxiety, stress, burnout, emotional distress, or another mental health condition related to or made worse by their work [ 11 ]. A mental health survey of orthopaedic team members in the United Kingdom during the COVID-19 pandemic found that the prevalence of GAD and MDD was almost three times and six times greater respectively than the general population [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…So, they were offered Balint training for 12 months, which enhanced their confidence by improving their psychological outlook and interest in patient care [ 18 ]. Thakrar et al also observed poor mental health among HCWs in emergency departments [ 19 ]. A cross-sectional multicentre study conducted in eight cities in Iran on obstetrics and gynaecology specialists managing pregnant patients infected with COVID-19 showed significantly higher scores on a questionnaire evaluating depression as compared to other healthcare practitioners.…”
Section: Discussionmentioning
confidence: 99%